PDTM-44. INTRACRANIAL EPENDYMOMA: DEVELOPING PRECLINICAL MODELS AND IDENTIFYING NOVEL TREATMENTS. (5th November 2018) - Lester, Ashleigh; Chung, Sylvia; Whittaker, Shane; Rapkins, Robert; McDonald, Kerrie
Abstract: INTRODUCTION: Clinical trials have not identified any effective chemotherapeutic treatments for intracranial ependymomas. This failure is partially explained by the recent identification of 6 molecularly distinct intracranial subgroups. Whilst subgroup specific preclinical investigations and treatments are required, these investigations have been hampered by the rarity of the tumours, failure to identify driver mutations for 5 of the subgroups, and difficulties establishing appropriate models. This study aims to establish patient derived cell lines, brain slice co-culture models and patient derived mouse models of intracranial ependymomas and utilise these models to identify and test novel subgroup specific drug treatments. METHODS/ RESULTS: Two patient-derived intracranial ependymoma cultures have been successfully established in neurobasal and serum free media, as adherent cells and neurospheres. Whole genome methylation sequencing and immunohistochemistry are being used to characterise the cultures. Brain slice co-culture models have been successfully created, with tumour cells growing on 200 µ M slices of brain from neo-natal mice. Cells dissociated from patient tumour tissue and matched low passage cultures have been injected intracranially into 25 mice, with evidence of tumours in three of the mice induced with cells from the first patient tumour. A screen of 111 approved drugs on ependymoma suspension cultures, has identified 4 drugs, including Bortezomib and Ponatinib, for further investigation in the established models. CONCLUSION: Patient-derived ependymoma cells can be successfully cultured as adherent cells, neurospheres, and in co-culture models. Subgrouping the samples, screening them against approved drugs, and testing potential drugs in patient-derived models is an effective mechanism for identifying candidate drugs for subgroups of these rare tumours.